Oxygen as an integral part of a healthy organism - N. M. Horobets; О. O. Alifer; У. Y. Dyvnych (Medicine of Ukraine, 2026)
The article discusses the role of oxygen in maintaining normal body functions, the mechanisms of gas exchange, and the main types of hypoxia. The importance of oxygen therapy for the prevention and correction of oxygen deficiency in cardiovascular, respiratory, and nervous system disorders, as well as during physical activity, pregnancy, and exposure to low-oxygen conditions, is highlighted. The potential use of the portable oxygen inhaler ACTIVOX as a convenient means of supporting adequate oxygenation and improving overall well-being is described.